2011
DOI: 10.1007/s00787-011-0211-3
|View full text |Cite
|
Sign up to set email alerts
|

Pain complaints as risk factor for mental distress: a three-year follow-up study

Abstract: The main aim of this study was to investigate the effect of pain complaints at baseline and mental distress at follow-up. We included adolescents from two longitudinal studies of 18/19 years of age with two corresponding cross-sectional baseline studies at age 15/16. A total of 5750 were invited for the baseline study, and we have 3-year follow-up data for 3316 (57.8% follow-up rate). All information is based on self-report. The questions of pain are asking for severe pain the past year. Mental distress is mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 30 publications
3
14
0
5
Order By: Relevance
“…The high prevalence of musculoskeletal pain, mental health problems, and their association is in accordance with earlier studies [2-4,9-11,16,39], with similar findings as a comparable survey done in other Norwegian counties [3,39]. A matter of concern was the high number of females with more than one pain site who reported above the clinical cut-off for anxiety/depression.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The high prevalence of musculoskeletal pain, mental health problems, and their association is in accordance with earlier studies [2-4,9-11,16,39], with similar findings as a comparable survey done in other Norwegian counties [3,39]. A matter of concern was the high number of females with more than one pain site who reported above the clinical cut-off for anxiety/depression.…”
Section: Discussionsupporting
confidence: 91%
“…Physical complaints are associated with anxiety/depressive symptoms [1,10-13], low self-esteem, poor resilience [14], peer-, parental-, or school problems [15-18]. A dose–response association between the number of pain sites and mental health problems has been found in adolescents [3], which is similar to the general population where multiple pains are associated with depression [19]. Most studies have examined the association between physical complaints and only a few psychosocial factors.…”
Section: Introductionmentioning
confidence: 99%
“…Research on paediatric community samples has shown that older children and adolescents with multiple, recurrent health complaints [9-13] –mainly headache and abdominal pains [14], as well as musculoskeletal symptoms [15] and fatigue [16]– have an amplified risk to experience anxiety and depressive symptoms. The above outcomes have been corroborated by longitudinal research evidence [5,17-23], even though not consistently [12,23-25]. Regarding the associations of SHC with externalizing symptoms and disorders, such as hyperactivity/inattention, conduct problems and difficulties in social interactions, research so far has been less extensive and less conclusive in its findings.…”
Section: Introductionmentioning
confidence: 96%
“…Increasing numbers of SHC have been associated with higher levels of anxiety and depressive symptoms, as well as of externalizing symptoms, signaling a shift of research focus from specific types of symptoms to the number and frequency of co-occurring symptoms [12,21,23,35]. Against this background, presentations of multiple, recurrent SHC in paediatric primary care services could foster the early identification of individuals with an elevated risk for emotional/behavioural problems and, thus, represent a viable window for timely mental health interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Musculoskeletal pain is a common complaint in adolescents (King et al, 2011;Mangerud et al, 2013;Eckhoff and Kvernmo, 2014), and adolescent multisite pain is more associated with mental health problems than single-site pain (Hoftun et al, 2011;Lien et al, 2011;Eckhoff and Kvernmo, 2014;Skrove et al, 2015). Adolescent musculoskeletal pain is associated with mood and anxiety disorders (Mangerud et al, 2013;Shanahan et al, 2015;Eckhoff et al, 2017), the most prevalent mental health disorders resulting in long-term medical benefits in Norway (Bragstad and Brage, 2011).…”
Section: Introductionmentioning
confidence: 99%